2019
DOI: 10.1155/2019/7312842
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effect ofTetragonia tetragonoides (Pall.) KuntzeExtract on Serotonin Turnover

Abstract: Tetragonia tetragonoides (Pall.) Kuntze (TTK) is a groundcover found along coastal areas of the Korean peninsula. TTK is traditionally used to improve women’s health and treat gastrointestinal diseases. Use of herbal medicines in the treatment of mood disorders has recently been suggested as an alternative therapeutic strategy. In the present study, we determined that consumption of TTK extract ameliorated progression of depressive-like symptoms in ovariectomized (OVX) rats and further examined the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Therefore, we speculated that the probiotic mixture ameliorated cisplatin-induced mucositis and pica in rats partly by normalizing the dysbiosis-driven 5-HT overproduction. Additionally, probiotic bacterial species and probiotic supplements have a tendency to directly reduce colonic 5-HT [69,70]. We confirmed that the probiotic mixture also had direct inhibitory effects against 5-HT biosynthesis in EC cells in vitro.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, we speculated that the probiotic mixture ameliorated cisplatin-induced mucositis and pica in rats partly by normalizing the dysbiosis-driven 5-HT overproduction. Additionally, probiotic bacterial species and probiotic supplements have a tendency to directly reduce colonic 5-HT [69,70]. We confirmed that the probiotic mixture also had direct inhibitory effects against 5-HT biosynthesis in EC cells in vitro.…”
Section: Discussionsupporting
confidence: 71%
“…TTK was reported to prevent obesity and hyperuricemia in obese mice induced by a high-fat diet [19], improve the energy and glucose metabolism in estrogen-deficient rats [13], and increase the anti-inflammatory activity [17]. Moreover, it has antidepressant activity with increasing serotonin concentrations by decreasing the serotonin reuptake activity [20]. These results suggest that TTK might improve the memory deficit induced by neuroinflammation and insulin resistance.…”
Section: Discussionmentioning
confidence: 94%
“…In the previous study, 1% and 2% TTK 70% ethanol extract decreased the immobility time in ovariectomized rats [ 27 ]. In this study, oral administration of 100 mg/kg and 300 mg/kg 30% ethanol extracts showed the antidepressant-like effect in the L-AAA induced depression model.…”
Section: Discussionmentioning
confidence: 99%
“…70% ethanol extract of TTK demonstrated potential to treat menopause-associated symptoms and metabolic disturbances [ 26 ]. Moreover, TTK extract ameliorated the depressive-like symptoms and regulated the serotonin level in ovarietomized rats [ 27 ]. The antidepressant effect of TTK in the depressive models has not been tested, and previous studies indicated the possibility that TTK may be effective on treating depressive disorders.…”
Section: Introductionmentioning
confidence: 99%